Influence of Hall Current and Chemical Reaction on MHD Unsteady Mass and Heat Transfer Flow Under Rotation - Mahanta, Maushumi; Sinha, Sujan (Communications in Mathematics and Applications, 2023)
A literal explanation on the dilemma about a transient MHD heat and mass transfer flow under Hall current and chemical reaction past a uniformly accelerated porous plate influenced by magnetic intensity with rotation has been presented. Having assumed a magnetic field with uniform intensity, it is applied perpendicular to the plate oriented to the fluid region. The governing equations of flow are solved analytically by adopting Laplace transform technique in closed form. The profiles of concentration field and Sherwood number concerning the plate are graphically verified with respect to different values of the parameters involving the problem. The consequent results have been explained physically. It is observed that consumption of chemical species leads to fall in species concentration.